(untitled) - Kugbei, Sam (Aleppo, Syria, 2000)
Information on the economics of seed production and seed technology are presented. Subjects include: (1) the development of the seed industry in industrialized and developing countries; (2) technical aspects of seed production such as quality control and pricing policies; (3) institutional arrangements such as national seed projects, seed corporations, seed boards, credit systems, seed associations and co-operatives; (4) financial viability analysis; (5) economic analysis; (6) social and environmental impact analysis; (7) components of cost structure including field-level seed multiplication costs; (8) cost monitoring, control, and planning; (9) steps in privatizing state-owned seed companies; (10) formation of small-scale seed enterprises; (11) roles of public and private investment in seed provision; and (12) organization and financial management of enterprises
Keywords: Seed industry and trade,Industrial management; Developing countries.,Developing countries